Architecture for integrated RF photonic downconversion of electronic signals - O'Malley, Nathan P; McKinzie, Keith A; Alshaykh, Mohammed S; Liu, Junqiu; Leaird, Daniel E; Kippenberg, Tobias J; McKinney, Jason D; Weiner, Andrew M (Optics letters, 2023)
Electronic analog to digital converters (ADCs) are running up against the well-known bit depth versus bandwidth trade off. Towards this end, radio frequency (RF) photonic-enhanced ADCs have been the subject of interest for some time. Optical frequency comb technology has been used as a workhorse underlying many of these architectures. Unfortunately, such designs must generally grapple with size, weight, and power (SWaP) concerns, as well as frequency ambiguity issues which threaten to obscure critical spectral information of detected RF signals. In this work, we address these concerns via an RF photonic downconverter with potential for easy integration and field deployment by leveraging a novel, to the best of our knowledge, hybrid microcomb/electro-optic comb design.